Memodelkan Impor Beras Menggunakan Regresi Data Panel - Kencana, Eka N; Arnawa, Darma; Jayanegara, Ketut (Jurnal Matematika, 2021)
Abstract Rice is one of the world’s most important commodities. The Food and Agri- cultural Organizations estimates about 90 percent of the world’s rice is produced by countries in the Asian continent with the rice production centers located in the ASEAN region. As an agricultural country, Indonesia is ranked third in the world rice producers after China and India, and in the first rank of ASEAN rice producers. However, Indone- sia along with other producing countries in ASEAN also import rice. This article aims to model rice imports from 5 ASEAN countries. Using data from FAO for the period 2009–2018, 3 types of Panel Data Regression models were applied to model rice imports. The results of the analysis show Random Effect Model (REM) is the most appropriate model for rice imports in 5 ASEAN countries with the difference for two consecutive years import, consumption, and rice production was used as explanatory variables . Keywords: import, panel data, random effect, regression, rice.